Factor Mobility, Government Debt and the Decline in Public Investment - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper tries to explain the declining level of public investment in OECD countries. The theoretical framework hints to the relevance of a number of demand and supply factors – ranging from the yield of public investment to institutions like the EU deficit limits. The econometric results indicate that the decline is largely due to two developments: First to the pile-up of public debt since the 70s which in the 90s severely restricted ability to finance new investment. Second to the increasing mobility of factors that has added to the financing difficulties. In contrast to that neither the privatisation process nor EU deficit restrictions of the Maastricht Treaty can explain the decline.
Keywords: H50; H87; H63; 330; public investment; factor mobility; globalisation; public debt; OECD; EU; Öffentliche Investition; Haushaltskonsolidierung; Faktormobilität; Standortwettbewerb; OECD-Staaten; EU-Staaten